Otimização do processo de produção de biodiesel pelas rotas convencional e in situ a partir das amêndoas do Dipterix alata Vog (baru) utilizando Metodologia de Superfície de Resposta - Pereira, Nilson Roberto (2015)
This work presents the results obtained for the production of ethyl biodiesel through transesterification reaction in situ from Dipterix almonds alata vog (baru). The physicochemical characterization of baru seed was conducted and showed that this seed is suitable for submission to the reaction of alkaline transesterification in situ. Its low content of free fatty acids discards need to be made in advance esterification. The response surface methodology applied to the experimental results enabled display regions leading to maximum biodiesel production yield. For the in situ reaction has been observed maximum yield of 40.2% when the reaction has proceeded to 45 °C, 0.8% and 25:1 for the following variables: temperature, catalyst concentration and molar ratio ethanol / oil, respectively. In contrast, the reaction of transesterification performed with the extracted oil obtained Baru maximum yield of 83% when the values of temperature, catalyst concentration and molar ratio ethanol: oil were 42 °C, 1.5% and 7:1 respectively . Moreover, four antioxidants were analyzed (guaiacol, curcumin and vanillin TBHQ) using the Rancimat equipment. Of these, only curcumin and TBHQ reached the time set by the specification required by the ANP. It was observed that addition at a concentration of 1000 ppm of curcumin achieved a time of 6 hours and 21 hours induction TBHQ. The relevance of this work is justified by the economy in getting baru biodiesel by the route in situ, and the elimination of the steps of extraction and oil refining it possible to reduce the cost of raw materials. Given the above, this study has the main objective to contribute to the development of new techniques that contribute to the improvement in the economic viability of the biodiesel production process.